Phylogenetic reconstruction of Schefflera J.R Frost & G. Frost in Borneo based on ITS regions of the nuclear genome. - Muhammad Raimi, Bin Mohd Fauz (Universiti Malaysia Sarawak (UNIMAS), 2015)
SchefJlera is the largest genus in the family Araliaceae. Asian SchejJlera group is one of the biggest and possibly most complex SchefJlera taxon in Araliaceae. Previous study on Asian SchefJlera group focusing more on Schefflera found in Borneo revealed that Schefflera in Borneo is not monophyletic. In this study, several SchejJlera species were collected from Batang Ai, Sarawak were used to reconstruct the phylogeny of Schefflera in Borneo. Species collected were extracted, amplified and sequenced using Internal Transcribed Spacer (ITS) of the nuclear region. Phylogenetic analyses using Maximum Parsimony (MP) and Maximum Likelihood (ML) were carried out. From the results obtained, Schefflera from Borneo are not monophyletic. Schefflera species from Sarawak are also not monophyletic and are placed within the Asian clade . Although the Schefflera species are collected from the same location, they are not from same lineage.